The visual perception of people with Autism Spectrum Disorder and its implications: an approach from Gestalt (Research, Society and Development, 2022)
Visual perception is associated with the learning and development of social communication, and Gestalt is a set of visual principles used to support the theory of visual perception based on the psychology of form. Cognition involves a mental process that allows our body to visualize images and mental concepts through the senses, and that enable us to reason, create, express and survive. People with Autism Spectrum Disorder (ASD) have sensory dysfunctions, mostly manifested through hypersensitivity, which trigger numerous atypical behaviors and influence development and socialization. Design and art are seen as tools that use communicative interfaces and interfere in visual and cognitive development in relation to the environment and learning. This article promotes the discussion and elucidation of the theme from a bibliographic review focusing on visual perception and Gestalt, reflecting on the impacts of these on the understanding of a neurodiverse mind. It aims to enable an observation and evaluation on the application of visual language more effectively, covering communication in a more inclusive and assertive way.